Controle químico de plantas aquáticas: Polygonum lapathifolium - Terra, M.a. [UNESP] (2003)
The objective of this trial was to study the efficacy of some herbicides in controlling P. lapathifolium. The experiment was carried out at Núcleo de Pesquisas Avançadas em Matologia of the Faculdade de Ciências Agronômicas/Botucatu - São Paulo, Brazil. Polygonum lapathifolium plants were collected in the Tietê River and cultivated in 0.6 x 0.6 x 0.45 m fiber glass tanks containing 15 cm of soil. The herbicides used were 2,4-D amine at 720 and 1,440 g e.a. ha-1, diquat at 480 g a.i. ha-1, glyphosate at 2,400 and 3,360 g e.a. ha-1 + Aterbane 0.5% v/v, imazapyr at 250 and 500 g i.a. ha-1 and an untreated plot. The application was carried out using a backpack sprayer pressurized with CO2 at 2,0 bar equipped with 2 flat fan nozzles type TeeJet XR110.02 VS. The application volume was 200 L ha-1. The experiment was arranged in a completely randomized design, with 3 replications. Visual evaluations were conducted by grading the injury symptoms according to a percentage scale. The results showed that only glyphosate provided an excellent control of Polygonum lapathifolium even at the lowest rate, reaching 100% at 46 days after application. Diquat caused severe injuries initially but these symptoms disappeared and the plants sprouted along the evaluation periods.